Dual Effect of Nitrate Therapy for Cyclosporine-Induced Hypertension on Vascular and Platelet Morphofunctional Markers; An Animal Model - Reis, F. (2007)
The present study sought to evaluate the prevention and reversion effects of isosorbide-5-mononitrate (Is-5-Mn) on the development of hypertension (HT) and on the underlying vascular and platelet morphofunctional disturbances, using an animal model of cyclosporine (CsA)-induced HT. The following rat groups (n = 8) were tested: (1) a control group (orange juice, for 7 weeks); (2) the CsA group (5 mg/kg/d for 7 weeks); (3) the Is-5-Mn group (150 mg/kg/d, twice a day for 7 weeks); (4) the prevention group (Is-5-Mn + CsA) treated for 2 weeks with Is-5-Mn only and thereafter with both drugs for 7 weeks; (5) the curative group (CsA + Is-5-Mn) beginning 7 weeks after CsA and following thereafter with both drugs for 5 weeks. Blood pressure, lipid profile, vascular lesion, platelet aggregation and morphology, and platelet thromboxane A2/vascular prostacyclin equilibrium were evaluated. Is-5-Mn + CsA therapy prevented (systolic blood pressure [SBP]: 114.3 ± 1.9 mm Hg, P < .001; diastolic blood pressure [DBP]: 97.0 ± 3.3 mm Hg, P < .001) the CsA-induced HT (SBP: 146.2 ± 4.5 mm Hg, P < .001; DBP: 124.9 ± 4.5 mm Hg, P < .001 vs control: SBP: 111.6 ± 0.7 mm Hg; DBP: 94.6 ± 1.0 mm Hg), as well as the vascular lesion and the platelet morphofunctional disturbances. The curative group did not show attenuated CsA-induced BP increase; it showed further enhancement of the HT effect (SBP: 159.7 ± 5.5 mm Hg, P < .05; DBP: 132.8 ± 2.8 mm Hg), as well as worsened vascular lesions and platelet function, namely a disruption in the TXA2/PGI2 equilibrium. Our data suggested that Is-5-Mn therapy may be a valid choice to prevent the morphofunctional changes associated with CsA-induced HT, when used as a preventive therapy. A careful evaluation of the impact of nitrate therapy should be considered, particularly the negative effect on cardiovascular hemodynamics, when considering its use after previous CsA disturbances have been established.